Time value of money dan economic value of time - Zendania, Athaya; Setyani, Kartika (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The concept Time Value of Money states that the value of money today is more valuable than the value of the same money in the future. But in sharia principles there is no such thing as Time Value of Money. In sharia principles, it is better known as the Economic Value of Time, meaning that money actually has no time value, but has economic value. Then the Time Value of Money itself triggers the human desire to develop their money in various ways, one of which is property investment. The purpose of this study is to answer how the investment scheme is in the theory of Time Value of Money and Economic Value of Time. The method discussed here is a case study of property investment using a home ownership credit system using conventional and sharia platforms. From the research conducted, it was found that based on assumption case calculations from several banks, using KPR with the best choice, namely KPR BCA First, if prospective buyers have a preference for Islamic banks by considering Islamic economic principles, the best choice is KPR BTN Syariah. The P2P Lending funding scheme is not a good choice because of the high interest charged.